ADVANTAGES AND PROBLEMS OF DIGITALIZATION OF THE ECONOMY IN UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
This article describes the economy, its digitization, ways to pursue a digitization policy, the components of the economy, how much this sector is needed today, the various problems in it, ways to solve them and the prospects for the future.